Flood Ring Evidence and its Application to Paleoflood Hydrology of the Red River and Assiniboine River in Manitoba - St. George, Scott; Nielsen, Erik (Géographie physique et Quaternaire, 2002)
AbstractAlthough paleoflood records developed from tree rings are much shorter than those developed from geological evidence, their brevity is offset by their exceptional utility for dating floods to a specific year. Inundation at the beginning of the growing season disturbs cambial processes in riparian Quercus spp., causing unusual anatomical features to develop within the annual ring, including small earlywood vessels, disrupted flame parenchyma and less wood fiber. These features are most strongly developed near the tree base, and may be caused by disruptions of auxin flow. Anatomical flood signatures can be used to determine the frequency, magnitude and hydrological causes of past floods, and to identify the influence of potential forcing mechanisms. In the lower Red River basin, Canada, flood-ring evidence has been used to identify several large floods during the mid 1700s, the early to mid 1800s and the latter half of the 20th century. Records for the Assiniboine River and the American portion of the Red River are developed from fewer trees, but suggest that severe floods in the Red and Assiniboine basins have coincided, albeit infrequently, during the past 500 years.